Mind Over Matter: The Impact of Positive Thinking on Health Outcomes - Jummiati Ismail (PSPP JOURNALS, 2023)
This paper from the journal Health Psychology analyzes the connection between positive outlook and beneficial actions in young adults. Two hundred people between the ages of 18 and 25 participated in the poll that measured optimistic outlook and healthful actions. Positive thinking was found to be correlated with health-enhancing behaviors, indicating that encouraging positive thinking could be an effective method of encouraging healthy lifestyles and lowering the prevalence of chronic diseases. The research had some flaws, such as a small sample size and the fact that it relied on participants' own reports for its findings. To confirm these results and discover interventions that effectively promote healthy thinking and living, more study is required.